IMPLEMENTASI PELAYANAN BIMBINGAN KONSELING BERDASARKAN PANDUAN KEMENDIKBUD 2016 - Anniez Rachmawati Musslifah (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Guidance and Counseling Guidelines on Primary and Secondary Education issued by the Ministry of Education and Culture of the Republic of Indonesia in 2016 is one of the main modules of the implementation of guidance and counseling in Indonesia which is full of various studies. This paper aims to find out what indicators of the implementation of counseling guidance and the implementation of counseling guidance is in line with those indicators. The research conducted is normative or literatures studies research.Â The results of the analysis showed 4 (four) indicators in guidance and counseling services: first, through characteristics; second, through the interrelationship of developmental tasks and standards of self-reliance competencies, which focus on the suitability of levels and developmental tasks; third, through both test and non-test techniques; and fourth, through the utilization of assessment data as an evaluation material for students. In its implementation, guidance and counseling services focus on developments that are in line with the characteristics and duties of learners.